Mass drug administration of ivermectin, diethylcarbamazine, plus albendazole compared with diethylcarbamazine plus albendazole for reduction of lymphatic filariasis endemicity in Papua New Guinea: a cluster-randomised trial. Issue 8 (August 2022) - Laman, Moses; Tavul, Livingstone; Karl, Stephan; Kotty, Bethuel; Kerry, Zebede; Kumai, Stephen; Samuel, Anna; Lorry, Lina; Timinao, Lincoln; Howard, S Cade; Makita, Leo; John, Lucy; et al.
Summary: Background: A single co-administered dose of a triple-drug regimen (ivermectin, diethylcarbamazine, and albendazole) has been shown to be safe and more efficacious for clearing Wuchereria bancrofti microfilariae than the standard two-drug regimen of diethylcarbamazine plus albendazole in clinical trials. However, the effectiveness of mass drug administration with the triple-drug regimen compared with the two-drug regimen is unknown. We compared the effectiveness of mass drug administration with the triple-drug and two-drug regimens for reducing microfilariae prevalence to less than 1% and circulating filarial antigen prevalence to less than 2%, levels that are unlikely to sustain transmission of lymphatic filariasis, in Papua New Guinea. Methods: This open-label, cluster-randomised study was done in 24 villages in a district endemic for lymphatic filariasis in Papua New Guinea. Villages paired by population size were randomly assigned to receive mass drug administration with a single dose of the triple-drug oral regimen of ivermectin (200 μg per kg of bodyweight) plus diethylcarbamazine (6 mg per kg of bodyweight) plus albendazole (400 mg) or a single dose of the two-drug oral regimen of diethylcarbamazine (6 mg per kg of bodyweight) plus albendazole (400 mg). This is a follow-on study of a previously reported safety study (ClinicalTrials.gov NCT02899936 ). All residents aged 5 years or older and non-pregnant women were asked to participate. After cross-sectional night blood microfilariae and circulating filarial antigen surveys, mass drug administration was provided at baseline and repeated 12 months later. The primary outcomes were mean prevalence of microfilariae and circulating filarial antigen at 12 months and 24 months, assessed in all residents willing to participate at each timepoint. This study is registered with ClinicalTrials.gov, NCT03352206 . Findings: Between Nov 18, 2016, and May 26, 2017, 4563 individuals were enrolled in 24 clusters; 12 clusters (2382 participants) were assigned to the triple-drug regimen and 12 clusters (2181 participants) to the two-drug regimen. Mean drug ingestion rates (of residents aged ≥5 years) were 66·1% at baseline and 63·2% at 12 months in communities assigned to the triple-drug regimen and 65·9% at baseline and 54·9% at 12 months in communities assigned to the two-drug regimen. Microfilariae prevalence in the triple-drug regimen group decreased from 105 (4·4%) of 2382 participants (95% CI 3·6–5·3) at baseline to nine (0·4%) of 2319 (0·1–0·7) at 12 months and four (0·2%) of 2086 (0·1–0·5) at 24 months. In the two-drug regimen group, microfilariae prevalence decreased from 93 (4·3%) of 2181 participants (95% CI 3·5–5·2) at baseline to 29 (1·5%) of 1963 (1·0–2·1) at 12 months and eight (0·4%) of 1844 (0·2–0·9) at 24 months (adjusted estimated risk ratio 4·5, 95% CI 1·4–13·8, p=0·0087, at 12 months; 2·9, 95% CI 1·0–8·8, p=0·058, at 24 months). The prevalence of circulating filarial antigen decreased from 523 (22·0%) of 2382 participants (95% CI 20·3–23·6) at baseline to 378 (16·3%) of 2319 (14·9–17·9) at 12 months and 156 (7·5%) of 2086 (6·4–8·7) at 24 months in the triple-drug regimen group and from 489 (22·6%) of 2168 participants (20·7–24·2) at baseline to 358 (18·2%) of 1963 (16·7–20·1) at 12 months and 184 (10·0%) of 1840 (8·7–11·5) at 24 months in the two-drug regimen group; after adjustment, differences between groups were not significant. Interpretation: Mass administration of the triple-drug regimen was more effective than the two-drug regimen in reducing microfilariae prevalence in communities to less than the target level of 1%, but did not reduce circulating filarial antigen prevalence to less than 2%. These results support the use of mass drug administration with the triple-drug regimen to accelerate elimination of lymphatic filariasis. Funding: Bill & Melinda Gates Foundation.